Leptospirosis seropositivity and its serovars among cattle in Northeastern Malaysia - Daud, Aziah; Mohd Fuzi, Nik Mohd Hafiz; Arshad, Mohd Mokhtar; Kamarudin, Suratan; Wan Mohammad, Wan Mohd Zahiruddin; Amran, Fairuz; Ismail, Nabilah (2018)
Background: Leptospirosis is a zoonotic disease that infects human and livestock which causes economic losses to the farmers. It has been reported as one of the causes of reproductive failure in cattle and other ruminants, determining abortions,stillbirth, weak newborns, and decrease in their growth rate and milk production.